Qualitative research in conflict and humanitarian settings: Reflections on methodology, ethics, and value - Behrends, Andrea; Urbani, Ilaria (2025)
This Learning Note explores the methodological, ethical, and practical dimensions of conducting qualitative research in conflict and humanitarian settings. It highlights how long-term, context-sensitive approaches—such as participant observation and in-depth conversations—offer unique insights into displacement, recovery, and social transformation that quantitative data alone cannot capture. The note underscores the value of complementing qualitative depth with quantitative breadth, fostering triangulation and credibility. Central to this reflection are ethical considerations, including participant safety, cultural sensitivity, and researcher positionality, which demand reflexivity and adherence to the principle of “do no harm.” Drawing on anthropological perspectives, the note illustrates how localized knowledge, historical awareness, and sustained engagement can enrich humanitarian and development research. Ultimately, it argues that rigorous and ethically grounded qualitative inquiry is indispensable for understanding human agency and resilience in fragile contexts, and for informing more effective and respectful responses to crises.